The Effects of Non-pharmacological Program to Manage and Prevent Acute Delirium in Critically Ill Surgical Patients - Luenapa , Sawalee; Hiransai, Phunsuk; Chintapanyakun, Teepatad; Yutthasaen, Siwaphan; Thongpan, Supaporn; Manma , Juraiporn; Teerananukul, Wipavee (Journal of The Royal Thai Army Nurses, 2023)
This quasi-experimental research aimed to study the effects of non-pharmacological management and prevention program for acute delirium in postoperative critically ill patients. The participants were adult patients aged over 18 years old and admitted to two surgical intensive care units (3IC and SDICU 51), Faculty of Medicine Ramathibodi Hospital, Mahidol University. Data were collected from 100 postoperative critically ill patients. Fifty of the participants in the experimental group received non-pharmacological management and prevention program, while another 50 of the participants in the control group received usual care. The research instruments were the non-pharmacological management and prevention program for acute delirium and the Richmond agitation sedation scale assessment. Data were analyzed using descriptive and Chi-squares statistics. The results revealed that the program of non-pharmacological management and prevention for acute delirium had reduced the incidence of acute delirium at the significant level of .05 (p = .028) and incidence of unplanned extubation at the significant level of .05 (p = .041).